2017
DOI: 10.3390/f8110411
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal Patterns of Pine Wilt Disease in the Early Stage of Its Invasion in South Korea

Abstract: Abstract:We characterized the dispersal patterns of pine wilt disease (PWD) in the early stage of its invasion in the South Korea, and estimated the influence of environmental factors on the dispersal of PWD. Data were obtained in 10 regions with at least five consecutive years of data for 10 years from 1994 to 2005. The dispersal patterns of PWD were categorized into four types: type 1 is a jumping type of dispersal, forming new patches; type 2 infestations are ones without any expansion of patch size; and ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…These results show that the dispersal patterns of PWD are Type 2 based on Shigesada et al [41]. Choi et al [46] estimated the annual dispersal distance in South Korea to be 0.37 km, based on the annual changes of areas damaged by PWD in the early stages of invasion, and the annual dispersal distances were less than 1.0 km in most (88.8%) of damaged areas; they also showed that "jumping" was the dominant dispersal method in the early stages of the invasion, while later dispersal was due to the expansion of existing colonies. Dispersal speed increased with increasing human population density, suggesting human-mediated dispersal [66,67].…”
Section: Occurrence History and Ecologysupporting
confidence: 59%
See 3 more Smart Citations
“…These results show that the dispersal patterns of PWD are Type 2 based on Shigesada et al [41]. Choi et al [46] estimated the annual dispersal distance in South Korea to be 0.37 km, based on the annual changes of areas damaged by PWD in the early stages of invasion, and the annual dispersal distances were less than 1.0 km in most (88.8%) of damaged areas; they also showed that "jumping" was the dominant dispersal method in the early stages of the invasion, while later dispersal was due to the expansion of existing colonies. Dispersal speed increased with increasing human population density, suggesting human-mediated dispersal [66,67].…”
Section: Occurrence History and Ecologysupporting
confidence: 59%
“…The area damaged by the PNGM was the highest (351,679 ha) in 1971 and then gradually decreased to 73,206 ha by 2004 [14]. This might have been caused by several factors such as PNGM management and the development of natural enemies [12,46] PNGM density. The emergence rate increases with increasing soil water content, while it decreases with the decreasing water content [48].…”
Section: Occurrence History and Ecologymentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of invasive species has increased worldwide due to global warming and international trade [1][2][3]. At the beginning of the invasion process, the community containing the invasive species does not have appropriate species interactions, such as prey-predator, host-parasite, and competition between species to stabilize the community dynamics [4][5][6]. Therefore, they can cause a severe impact on the existing ecosystem, resulting in notorious pests in many countries [7], for example, the gypsy moth (Lymantria dispar L.), the Asian long horn beetle (Anoplophora glabripennis Motschulsky), the emerald ash borer (Agrilus planipennis Fairmaire), found in the USA [8], and the pine wood nematode (Bursaphelenchus xylophilus Steiner and Buhrer), which is found in many countries, including Korea and Japan [9,10].…”
Section: Introductionmentioning
confidence: 99%